2016
DOI: 10.1016/j.bpj.2016.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Insights into the Binding between the nSH3 Domain of CrkII and Proline-Rich Motifs in cAbl

Abstract: The interaction between CrkII and cAbl is implicated in diverse cellular processes. This interaction starts with the binding of the N-terminal Src homology 3 (nSH3) domain of CrkII to the proline-rich motifs of cAbl (PRMs). Despite its critical importance, the detailed binding mechanism between the nSH3 domain and PRMs remains elusive. In this study, we used nuclear magnetic resonance Carr-Purcell-Meiboom-Gill relaxation dispersion experiment to study the binding kinetics between the nSH3 domain of CrkII and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 69 publications
7
11
0
Order By: Relevance
“…The kinetic and equilibrium results from 1D 19 F lineshape analysis are consistent with other reports on SH3-peptide interactions (62,(79)(80)(81). The kinetic investigations (62,81) found that dissociation was more sensitive to temperature change than association, and the signs of the energetic terms were the same.…”
Section: Temperature Dependence Of Bindingsupporting
confidence: 90%
See 4 more Smart Citations
“…The kinetic and equilibrium results from 1D 19 F lineshape analysis are consistent with other reports on SH3-peptide interactions (62,(79)(80)(81). The kinetic investigations (62,81) found that dissociation was more sensitive to temperature change than association, and the signs of the energetic terms were the same.…”
Section: Temperature Dependence Of Bindingsupporting
confidence: 90%
“…The kinetic and equilibrium results from 1D 19 F lineshape analysis are consistent with other reports on SH3-peptide interactions (62,(79)(80)(81). The kinetic investigations (62,81) found that dissociation was more sensitive to temperature change than association, and the signs of the energetic terms were the same. Importantly, other reports used alternative techniques including isothermal titration calorimetry (80,81), fluorescence spectroscopy (62,79), ZZ-exchange NMR (81), and Carr-Purcell-Meiboom-Gill relaxation dispersion NMR (62,81).…”
Section: Temperature Dependence Of Bindingsupporting
confidence: 90%
See 3 more Smart Citations